Phosphorescent polymer and preparation method thereof and organic electroluminescent device

The phosphorescent polymer formed through electrostatic adsorption solves the problem of poor controllability of metal complex doping, achieves efficient, consistent production and diversified products, and improves the performance of organic electroluminescent devices.

CN115851265BActive Publication Date: 2025-03-04KUNSHAN GO VISIONOX OPTO ELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211473782.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-22
Publication Date
2025-03-04
Estimated Expiration
2042-11-22

AI Technical Summary

Technical Problem

The current phosphorescent polymer materials have poor controllability of metal complex doping, which affects its production efficiency and the long-term development of organic electroluminescent devices.

Method used

The formation of phosphorescent polymers is achieved through electrostatic adsorption between the polymer main body and the metal complex, ensuring the precise doping of heavy metal complex units, improving production efficiency and product consistency.

Benefits of technology

Accurate doping control of phosphorescent polymers is achieved, production efficiency and product consistency are improved, and the stability and diversity of organic electroluminescent devices are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115851265B_ABST
    Figure CN115851265B_ABST
Patent Text Reader

Abstract

The present invention provides a phosphorescent polymer and a preparation method thereof and an organic electroluminescent device. The phosphorescent polymer includes a polymer unit and a heavy metal complex unit, wherein the polymer unit includes a polymer main chain unit and a first side chain unit; the first side chain unit includes a quaternary ammonium cation, and the heavy metal complex unit includes a heavy metal complex anion for adsorbing the quaternary ammonium cation. The phosphorescent polymer is formed by adsorption through static electricity generated between the polymer main body and the metal complex, so the special electrostatic effect in the phosphorescent polymer can ensure the precise doping of the heavy metal complex therein, thereby ensuring the production consistency and product diversity of the organic electroluminescent device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a phosphorescent polymer and a preparation method thereof and an organic electroluminescent device, belonging to the technical field of organic electroluminescent. Background Art

[0002] An organic electroluminescent device is a device that is driven by electric current to emit light. Its main characteristics come from the organic light-emitting layer. When an appropriate voltage is applied, electrons and holes will combine in the organic light-emitting layer to produce excitons and emit light of different wavelengths according to the characteristics of the organic light-emitting layer.

[0003] In recent years, phosphorescent materials have become the preferred materials for the organic light-emitting layer in organic electroluminescent devices because they can effectively utilize singlet and triplet excitons to achieve 100% energy utilization efficiency compared to fluorescent materials. Phosphorescent polymer materials can be processed by solution spin coating, inkjet printing and other processing methods in the production process of organic electroluminescent devices. Therefore, compared with phosphorescent small molecule materials, phosphorescent polymer materials have lower time costs in production and better film-forming properties of the organic light-emitting layer.

[0004] However, current phosphorescent polymer materials generally have the defect of poor controllability of metal complex doping, which not only affects the production efficiency of phosphorescent polymers, but also is not conducive to the long-term development of organic electroluminescent devices. Summary of the invention

[0005] The present invention provides a phosphorescent polymer, which is formed by adsorption through static electricity generated between a polymer main body and a metal complex. Therefore, the special electrostatic effect in the phosphorescent polymer can ensure the precise doping of the heavy metal complex unit therein, which not only improves the production efficiency of the phosphorescent polymer material, but also ensures the production consistency and product diversity of organic electroluminescent devices.

[0006] The present invention also provides a method for preparing the phosphorescent polymer. The method is simple and easy to operate, does not require the assistance of large-scale equipment, and accelerates the mass production of the phosphorescent polymer.

[0007] The present invention also provides an organic electroluminescent device, wherein the light-emitting layer of the organic electroluminescent device comprises the phosphorescent polymer, so the organic electroluminescent device has the advantages of high product stability and strong product diversity.

[0008] The present invention provides a phosphorescent polymer, which includes a polymer unit and a heavy metal complex unit, wherein the polymer unit includes a polymer main chain unit and a first branch chain unit;

[0009] The first branch unit includes a quaternary ammonium cation, and the heavy metal complex unit includes a heavy metal complex anion for adsorbing with the quaternary ammonium cation.

[0010] Optionally, the phosphorescent polymer includes N first blocks as shown in Formula 1, N≥1,

[0011]

[0012] Where A is the repeating unit of the polymer main chain unit, R a + is the first branching unit including a quaternary ammonium cation, M - is a heavy metal complex unit including a heavy metal complex anion, and a1≥1.

[0013] Optionally, the phosphorescent polymer further comprises M second blocks as shown in Formula 2, M≥1,

[0014]

[0015] Among them, a2≥1.

[0016] Optionally, the phosphorescent polymer further comprises a third block of T species as shown in Formula 3 and / or a fourth block of Q species as shown in Formula 4, T≥1, Q≥1,

[0017]

[0018] Among them, B and C are the repeating units of the polymer main chain unit, R b is the second branch unit, b≥1, c≥1.

[0019] Optionally, the first branch unit and / or the second branch unit includes at least one group represented by Z-1, Z-2, Z-3, Z-4, Z-5, Z-6, Z-7 and Z-8.

[0020] Optionally, the total mass proportion of the third block and the fourth block in the phosphorescent polymer is greater than or equal to 50% and less than or equal to 80%; and / or,

[0021] The mass proportion of the second block in the phosphorescent polymer is greater than or equal to 10% and less than or equal to 45%; and / or,

[0022] More preferably, the mass proportion of the first block in the phosphorescent polymer is greater than or equal to 5% and less than or equal to 10%; and / or,

[0023] The molar percentage of the heavy metal complex unit in the phosphorescent polymer is less than or equal to 10%.

[0024] Optionally, the quaternary ammonium cation has a structure shown in Formula 5,

[0025]

[0026] Wherein, R1 to R3 are independently selected from C1 to C30 substituted or unsubstituted alkyl groups.

[0027] Optionally, the first excited triplet energy level of the polymer unit is not less than 2.62 eV; optionally, the polymer main chain unit is a non-conjugated structure.

[0028] The present invention also provides a method for preparing the above-mentioned phosphorescent polymer, comprising: stirring a solution comprising a polymer and a heavy metal complex to obtain a phosphorescent polymer, wherein the polymer is used to provide a polymer unit, and the heavy metal complex is used to provide a heavy metal complex unit. The present invention also provides an organic electroluminescent device, wherein the organic electroluminescent device comprises a light-emitting layer, and the light-emitting layer comprises the above-mentioned phosphorescent polymer.

[0029] The present invention also provides an organic electroluminescent device, comprising a light-emitting layer, wherein the light-emitting layer comprises any one of the phosphorescent polymers described above.

[0030] The phosphorescent polymer of the present invention comprises a polymer unit with a quaternary ammonium cation and a heavy metal complex unit with a heavy metal complex anion, and the combination of the polymer unit and the heavy metal complex unit is achieved through the electrostatic adsorption of the quaternary ammonium cation and the heavy metal complex anion, thereby obtaining the phosphorescent polymer of the present invention. Therefore, in the preparation process of the phosphorescent polymer, the specific ratio of the raw material for providing the polymer unit and the raw material for providing the heavy metal complex unit can be determined according to the target doping amount of the heavy metal complex unit, and finally the phosphorescent polymer meeting the target doping ratio is obtained. Therefore, the special composition of the phosphorescent polymer of the present invention builds a foundation for the precise control of the doping of the heavy metal complex unit, not only ensuring the production consistency of the same batch of phosphorescent polymers, improving the production efficiency of the phosphorescent polymer, but also being able to achieve the preparation of different phosphorescent polymers by establishing doping differentiation, realizing the production diversity of the phosphorescent polymer. Therefore, the special composition structure of the phosphorescent polymer is conducive to improving the production consistency, performance stability, and product diversity of organic electroluminescent devices, and promoting the development of organic electroluminescent devices.

[0031] In addition, the preparation method of the phosphorescent polymer is simple, easy to implement, safe and efficient, and suitable for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 PL spectrum diagram of the device of Example 1 of the present invention;

[0033] Figure 2 PL spectra of devices of Examples 2-6 of the present invention;

[0034] Figure 3 PL spectra of devices of comparative examples 7-11 of the present invention;

[0035] Figure 4 It is a comparison diagram of the brightness-current efficiency curves of the device of Example 1 of the present invention and the device of Comparative Example 1;

[0036] Figure 5 It is a comparison chart of the brightness-current efficiency curves of the device of Example 1, the device of Example 13 and the device of Example 16 of the present invention. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Compared with the evaporation method used by small molecule phosphorescent materials, phosphorescent polymer materials can be processed by solution spin coating, inkjet printing and other processing methods. Therefore, phosphorescent polymer materials have better film-forming properties and are more conducive to the production of organic electroluminescent devices. At present, phosphorescent polymer materials are mainly divided into two categories. One is to physically mix the heavy metal complex unit with the polymer main body, but this physical mixing method will cause the organic electroluminescent device to have phase separation problems during long-term use, resulting in a decrease in device life and luminous efficiency. The other is to polymerize the monomer including the heavy metal complex unit, and introduce the heavy metal complex unit into the main chain or side chain of the polymer. Although this method can overcome the defect of phase separation, since the polymerization reaction is a chain initiation reaction, the reaction process is difficult to control, so it is difficult to obtain a phosphorescent polymer with a heavy metal complex unit that meets the expected doping, which not only affects the production efficiency of the phosphorescent polymer, but also hinders the industrial production of the phosphorescent polymer.

[0039] Based on the above problems, the first aspect of the present invention provides a phosphorescent polymer, the phosphorescent polymer comprising a polymer unit and a heavy metal complex unit, the polymer unit comprising a polymer main chain unit and a first branch unit;

[0040] The first branch unit includes a quaternary ammonium cation, and the heavy metal complex unit includes a heavy metal complex anion for adsorbing with the quaternary ammonium cation.

[0041] The phosphorescent polymer of the present invention comprises a polymer unit and a heavy metal complex unit, wherein the polymer unit is the main body of the phosphorescent polymer, and the heavy metal complex unit is the light-emitting unit of the phosphorescent polymer. When holes and electrons combine to generate excitons, the polymer unit absorbs the exciton energy and transfers the exciton energy to the heavy metal complex unit, accompanied by the radiation deactivation of the first excited triplet energy of the heavy metal complex unit, thereby achieving effective electrophosphorescence. Specifically, the polymer unit of the present invention comprises a polymer main chain unit and a first branch unit, wherein the polymer main chain unit is formed by mutual polymerization of parts of the monomers used for substantial polymerization reaction, and the first branch unit does not participate in the substantial polymerization reaction, and only serves as a substituent group of the polymer main chain unit and finally manifests as a side chain of the polymer unit.

[0042] The first branch unit of the present invention includes a quaternary ammonium cation, and the heavy metal complex unit includes a heavy metal complex anion. Therefore, in the presence of the heavy metal complex anion and the quaternary ammonium cation, the heavy metal complex unit can undergo electrostatic adsorption with the first branch unit, so that the heavy metal complex unit is used as a part of the first branch unit to obtain the phosphorescent polymer of the present invention. The phosphorescent polymer of the present invention has extremely strong stability during application, avoids the defect of reduced service life caused by phase separation, and has stable and excellent performance in terms of life, driving voltage, efficiency, etc. during long-term use.

[0043] It is worth mentioning that the special electrostatic adsorption between the polymer unit and the heavy metal complex unit in the present invention is conducive to more accurate control of the doping ratio of the heavy metal complex unit in the phosphorescent polymer. The reason is that when preparing the phosphorescent polymer, the heavy metal complex unit can be prevented from participating in the polymerization reaction by controlling parameters such as raw material selection and step sequence. It is only necessary to select the corresponding monomers to polymerize each other into polymer units, and then control the ratio of the polymer unit and the heavy metal complex unit to achieve adsorption of the two and prepare a phosphorescent polymer with a target doping ratio of the heavy metal complex unit.

[0044] Therefore, the special composition structure of the phosphorescent polymer of the present invention can accurately control the doping ratio of the heavy metal complex unit therein, and finally ensure that the phosphorescent polymer has a target doping ratio of the heavy metal complex unit, avoiding the defect of difficulty in controlling the content of the heavy metal complex unit in the phosphorescent polymer caused by the polymerization reaction of the monomer containing the heavy metal complex unit. The special composition of the phosphorescent polymer of the present invention accurately ensures the doping ratio of the heavy metal complex unit in the phosphorescent polymer, so it can not only achieve the consistency of the same batch of products and improve the production efficiency, but also facilitate the construction of differentiation of the phosphorescent polymer in the doping of the heavy metal complex unit, thereby achieving product diversity.

[0045] The present invention does not limit the composition of the polymer unit, which can be formed by the polymerization of any monomers that can undergo polymerization and contain a substituent of a quaternary ammonium cation. The present invention also does not limit the substituent containing a quaternary ammonium cation, for example, it can be a C1-C10 alkyl group, a C6-C30 aryl group, a C2-C30 heteroaryl group, etc. It can be understood that in addition to being substituted by a quaternary ammonium cation, the substituent can also contain other substituents such as halogen, nitro, hydroxyl, cyano, etc.

[0046] In addition, the present invention does not impose any special restrictions on the heavy metal complex unit, as long as it can emit phosphorescence. For example, it can be a common iridium complex in the art shown in the following A to P, for example, it can be a cyano iridium complex.

[0047]

[0048]

[0049] The present invention does not impose any particular limitation on the molecular weight of the phosphorescent polymer, and a suitable molecular weight can be selected as required.

[0050] In a possible implementation, the phosphorescent polymer includes N first blocks as shown in Formula 1, where N≥1.

[0051]

[0052] Where A is the repeating unit of the polymer main chain unit, R a + is the first branching unit including a quaternary ammonium cation, M - is a heavy metal complex unit including a heavy metal complex anion, and a1≥1. The number of the first block may be one or more, which is not limited in the embodiment of the present invention.

[0053] The first block shown in Formula 1 is the first branched unit R containing a quaternary ammonium cation. a +A block that undergoes electrostatic adsorption with a heavy metal complex unit containing a heavy metal complex anion, wherein A is a repeating unit of a polymer main chain unit, which can be understood as being obtained by polymerization of a functional group participating in a polymerization reaction in a monomer; R a + The side chain substituent containing a quaternary ammonium cation in the monomer that does not participate in the polymerization reaction. For example, the monomer can be an ethylene or aryl phosphine oxide derivative or an aryl ether derivative with a side chain substituent, and the side chain substituent contains a quaternary ammonium cation. In addition, in addition to the first branch unit containing a quaternary ammonium cation, the polymer unit in the first block can also have other branch units that do not contain a quaternary ammonium cation.

[0054] It should be explained that the first block shown in Formula 1 refers to the block after electrostatic adsorption occurs, that is, as long as the block has electrostatic adsorption, it can be represented by Formula 1. When the phosphorescent polymer includes multiple first blocks of different compositions (blocks with electrostatic adsorption), the multiple first blocks of different compositions can be represented by Formula 1. Exemplarily, when N=1, there is only one first block with electrostatic adsorption shown in Formula 1 in the phosphorescent polymer; when N>1, the phosphorescent polymer has N first blocks with electrostatic adsorption shown in Formula 1, and the N first blocks are different from each other. Taking N=3 as an example, among the three first blocks, at least two of them may have different A (specifically, different monomers undergoing polymerization reaction during preparation), or at least two of them may have different R a + different (specifically, during the preparation, the side chain substituents of the monomers undergoing the polymerization reaction are different), or at least two M - Different (specifically, during preparation, the metal complexes subjected to electrostatic adsorption are different).

[0055] When N>1, the present invention does not limit the distribution of the N first blocks, and they can be distributed in any manner. Taking N=3 as an example, the three different first blocks are represented as I1, I2 and I3, respectively, and can be I1-I2-I3, I2-I1-I3, I3-I1-I3-I2, etc.

[0056] In another possible implementation, based on the above embodiment, the phosphorescent polymer further includes M second blocks as shown in Formula 2, where M≥1.

[0057]

[0058] Where a2≥1. In formula 2, A, R a + and M - The definition of is the same as that of Formula 1.

[0059] It can be understood that based on the doping ratio of the polymer unit and the heavy metal complex unit, there is a situation where the heavy metal complex unit and the first branch unit are not in equal proportion. In this case, the phosphorescent polymer will also include a second block as shown in Formula 2, which is a block of the first branch unit that does not adsorb the heavy metal complex unit. The number of the second block can be one or more, and the embodiment of the present invention is not limited to this.

[0060] Similarly, the second block shown in Formula 2 refers to a block that does not undergo electrostatic adsorption, that is, any block that has a first branch unit but does not undergo electrostatic adsorption can be represented by Formula 2. When the phosphorescent polymer includes multiple second blocks of different compositions, the multiple second blocks of different compositions can be represented by Formula 2. For example, when M=1, there is only one second block shown in Formula 2 in the phosphorescent polymer; when M>1, the phosphorescent polymer has M second blocks shown in Formula 2, and the M second blocks are different from each other. Taking M=3 as an example, at least two of the three second blocks may have different A (specifically, different monomers undergoing polymerization during preparation), or at least two of the R a + Different (specifically, during the preparation, the side chain substituents of the monomers undergoing the polymerization reaction are different).

[0061] When M>1, the present invention does not limit the distribution of the M second blocks, and they can be distributed in any manner. Taking M=3 as an example, the three second blocks are represented as II1, II2 and II3, respectively, and can be II1-II2-II3, II2-II1-II3, II2-II1-II2-II3, etc.

[0062] Further, based on the above two possible implementations, the phosphorescent polymer of the present invention further comprises T third blocks as shown in Formula 3 and / or Q fourth blocks as shown in Formula 4, T≥1, Q≥1,

[0063]

[0064] Among them, B and C are the repeating units of the polymer main chain unit, R b is the second branch unit, b≥1, c≥1.

[0065] The third block shown in Formula 3 is a block containing the second branch unit R b Specifically, B is a repeating unit of the polymer main chain unit, which can be understood as being obtained by polymerization of the functional groups participating in the polymerization reaction in the monomer; R bIt is a side chain substituent in the monomer that does not participate in the polymerization reaction and does not contain anions or cations. For example, the monomer can be ethylene or an aryl phosphine derivative or an aryl ether derivative with a side chain substituent, and the side chain substituent does not contain any anions or cations. The number of the third block can be one or more, which is not limited in the embodiment of the present invention. The number of the fourth block can be one or more, which is not limited in the embodiment of the present invention.

[0066] Since the third block does not include quaternary ammonium cations, there will be no adsorption of heavy metal complex units in the block. Therefore, as long as the block has a second branch unit, it can be represented by Formula 3, that is, when the phosphorescent polymer includes a plurality of third blocks of different compositions, the third blocks of various compositions can be represented by Formula 3. For example, when T=1, there is only one third block of Formula 3 in the phosphorescent polymer; when T>1, the phosphorescent polymer has T third blocks of Formula 3, and the T third blocks are different from each other. Taking T=3 as an example, among the three third blocks, at least two of them may have different B (specifically, different monomers undergoing polymerization during preparation), or at least two of them may have different Rb (specifically, different side chain substituents of the monomers undergoing polymerization during preparation).

[0067] When T>1, the present invention does not limit the distribution of the T third blocks, and they can be distributed in any manner. Taking T=3 as an example, the three third blocks are represented as III1, III2 and III3, respectively, and can be III1-III2-III3, III3-III1-III2, III2-III1-III2-III3-III1, etc.

[0068] In addition, the fourth block shown in Formula 4 is a block without a branch unit. Specifically, C is a repeating unit of the polymer main chain unit, which can be understood as being obtained by polymerization of the functional groups participating in the polymerization reaction in the monomer, and the monomer does not have any side chain substituents. For example, the monomer can be ethylene or an aryl phosphine oxide derivative or an aryl ether derivative.

[0069] In the present invention, any block without a side chain substituent can be represented by Formula 3, that is, when the phosphorescent polymer includes a plurality of fourth blocks of different compositions, the fourth blocks of different compositions can be represented by Formula 4. For example, when Q=1, there is only one fourth block of Formula 4 in the phosphorescent polymer; when Q>1, the phosphorescent polymer has Q fourth blocks of Formula 4, and the Q fourth blocks are different from each other. Taking Q=3 as an example, at least two of the three fourth blocks have different C (specifically, different monomers undergoing polymerization during preparation).

[0070] When Q>1, the present invention does not limit the distribution of the Q fourth blocks, and they can be distributed in any manner. Taking Q=3 as an example, the three fourth blocks are represented as IV1, IV2 and IV3, respectively, and can be IV1-IV2-IV3, IV3-IV1-IV2, IV2-IV1-IV2-IV3, etc.

[0071] It should be noted that in the blocks represented by the above formulae 1 to 4, A, B, and C are selected independently of each other, that is, they can be identical to each other, partially identical to each other, or different from each other. a and R b Independent selection (R a YesR a + refers to the group not substituted by the quaternary ammonium cation).

[0072] Similarly, when the phosphorescent polymer of the present invention includes at least two blocks of Formulae 1 to 4, the present invention does not impose any particular limitation on the distribution of the blocks, and the specific definition of the distribution is as described above.

[0073] Since both the first block and the second block are charged, the introduction of uncharged third blocks and / or fourth blocks into the phosphorescent polymer is beneficial to weaken the conductivity of the phosphorescent polymer, thereby having a positive effect on the luminescent properties and electrical properties (such as device life, luminescent efficiency, color purity, driving voltage, etc.) of the organic electroluminescent device containing the phosphorescent polymer.

[0074] In a specific embodiment, the first branch unit and / or the second branch unit includes at least one group represented by Z-1, Z-2, Z-3, Z-4, Z-5, Z-6, Z-7 and Z-8:

[0075]

[0076]

[0077] In the above structural formula, Represents a chemical bond bonded to the polymer main chain unit. The inventors have found that when at least one of the first branch unit and the second branch unit includes at least one group shown in the above Z-1, Z-2, Z-3, Z-4, Z-5, Z-6, Z-7 and Z-8, the efficiency of the organic electroluminescent device is significantly improved. The above structure helps to improve the steric hindrance of the molecular structure, avoid the phenomenon of exciton quenching due to mutual collision between molecules, and suppress the efficiency roll-off.

[0078] When the phosphorescent polymer of the present invention includes the third block and / or the fourth block, in one possible embodiment, the total mass proportion of the third block and the fourth block in the phosphorescent polymer is greater than or equal to 50% and less than or equal to 80%, that is, 50-80% (if the phosphorescent polymer includes the third block but does not include the fourth block, in one possible embodiment, the total mass proportion of the third block in the phosphorescent polymer is 50-80%, if the phosphorescent polymer includes the fourth block but does not include the third block, in one possible embodiment, the total mass proportion of the fourth block in the phosphorescent polymer is 50-80%, if the phosphorescent polymer includes the third block and the fourth block, in one possible embodiment, the total mass proportion of the third block and the fourth block in the phosphorescent polymer is 50-80%); and / or,

[0079] The mass proportion of the second block in the phosphorescent polymer is greater than or equal to 10% and less than or equal to 45%; and / or,

[0080] The mass proportion of the first block in the phosphorescent polymer is greater than or equal to 5% and less than or equal to 10%; and / or,

[0081] The molar percentage of the heavy metal complex unit in the phosphorescent polymer is less than or equal to 10%.

[0082] The inventors have found that when the quaternary ammonium cation has the structure shown in Formula 5, it is beneficial to more efficiently ensure the efficient adsorption of the heavy metal complex unit and the first branch unit, thereby facilitating more precise control of the doping ratio of the heavy metal complex unit.

[0083]

[0084] In Formula 5, R1 to R3 are independently selected from C1 to C30 substituted or unsubstituted alkyl groups, represents a chemical bond to the first branch unit. The substituents of R1 to R3 may be, for example, halogen, nitro, hydroxyl, cyano, amino, and the like.

[0085] Preferably, R1 to R3 are the same as each other and are unsubstituted alkyl groups, and more preferably, R1 to R3 are all methyl groups.

[0086] As mentioned above, the present invention does not limit the specific selection of the heavy metal complex unit, for example, it can be one or more of a heavy metal complex unit for emitting red phosphorescence, a heavy metal complex unit for emitting green phosphorescence, and a heavy metal complex unit for emitting blue phosphorescence. The phosphorescent polymer can be a red phosphorescent polymer, a green phosphorescent polymer, or a blue phosphorescent polymer. When the phosphorescent polymer is used to emit blue phosphorescence, since the emission of blue phosphorescence requires higher energy than red and green phosphorescence, it is necessary to select a more suitable polymer unit as the main body to match the heavy metal complex unit for emitting blue phosphorescence. Specifically, a polymer unit having a first excited triplet energy level greater than or equal to 2.62 eV can be selected.

[0087] Exemplarily, when the polymer unit includes at least one block shown below, a polymer unit having a first excited triplet energy level greater than or equal to 2.62 eV can be formed. For example, a suitable monomer can be selected during the preparation process to obtain a polymer unit including the following blocks. It should be noted that since the quaternary ammonium cation and the heavy metal complex anion have no significant effect on the first excited triplet energy level of the block, the first block of the phosphorescent polymer of the present invention does not include the part of the quaternary ammonium cation and / or the heavy metal complex anion, the second block does not include the part of the quaternary ammonium cation and / or the heavy metal complex anion, and the third block can all be at least one of the following ah (angle number x, a, b, c, d, n>1).

[0088]

[0089] It can be found that the above blocks are all non-conjugated structures. This non-conjugated structure has higher energy, which is beneficial to improve the first excited triplet energy level of the polymer unit to ensure the emission of blue light. For example, a polyethylene chain is used as the main chain of the phosphorescent polymer, and mCP (methylcyclopentenol ketone, 2-hydroxy-3-methyl-2-cyclopentene-1-one) is connected to the branch chain (side chain). Since a conjugated main chain is not used, the phosphorescent polymer has a higher triplet energy level and can be used as a blue light host. A quaternary ammonium salt group with positive charge is introduced at the 3-position of carbazole, and the negatively charged cyanoiridium complex can be attracted in the aqueous solution through ion exchange. The conditions are mild, the reaction time is short, and no heating is required, so the Dopant content can be accurately controlled. As shown in the following compound structure (angles x, y, z>1).

[0090]

[0091] In addition, relative to the non-conjugated structure shown in formula ag that does not contain any double bonds (for example, using a polyethylene chain as the main chain of the polymer), the non-conjugated structure shown in formula h in which the direct conjugation between aromatic rings is interrupted by a phosphorus-oxygen bond or an ether bond, in addition to having a higher first excited triplet energy level, is also beneficial to the migration of carriers in the organic electroluminescent device, thereby improving the luminous efficiency of the organic electroluminescent device by increasing the recombination rate of carriers.

[0092] Exemplarily, aromatic phosphine oxide derivatives and / or aromatic ether derivatives are used as the main chain of the phosphorescent polymer, as shown in the following compound structure (angle number x, a, b, c, d, n>1). Compared with the polymer structure directly linked to the benzene ring, the introduction of -P=O and -O- groups can effectively interrupt the conjugation between the aromatic rings, so that the polymer can have a higher triplet energy level and better carrier migration ability. The introduction of a positively charged quaternary ammonium salt group at the 3-position of carbazole can attract negatively charged cyanoiridium complexes through ion exchange in aqueous solution. The conditions are mild, the reaction time is short, and no heating is required, so that the Dopant content can be precisely controlled.

[0093]

[0094] The second aspect of the present invention further provides a method for preparing the phosphorescent polymer of the first aspect. The method comprises:

[0095] The solution including the polymer and the heavy metal complex is stirred to obtain the phosphorescent polymer, wherein the polymer is used to provide polymer units, and the heavy metal complex is used to provide heavy metal complex units.

[0096] The polymer includes a polymer unit and an anion compatible with the quaternary ammonium cation in the polymer unit, and the anion forms a quaternary ammonium salt with the quaternary ammonium cation through an ionic bond; the heavy metal complex includes a heavy metal complex unit and a cation compatible with the metal anion in the metal complex unit, and the cation forms a heavy metal complex with the heavy metal complex anion through an ionic bond. Both the polymer and the heavy metal complex can be purchased commercially or prepared by oneself.

[0097] In the specific preparation process, it is only necessary to mix and stir the polymer and the heavy metal complex unit in a solvent, and the anions in the polymer and the cations in the heavy metal complex will dissolve in the solution, thereby causing mutual adsorption of the quaternary ammonium cations and the heavy metal complex anions. The phosphorescent polymer of the present invention is obtained by concentrating, washing and drying the mixed system.

[0098] In a possible implementation, the above reaction is carried out at 25±5° C., with a stirring time of 30-300 min and a stirring speed of 300 r / min.

[0099] Furthermore, the solvent used to mix the polymer and the heavy metal complex unit may be a mixture of tetrahydrofuran and water, wherein the volume ratio of tetrahydrofuran (THF) to water is 1:1.

[0100] The preparation method of the present invention is simple and easy to operate, does not require the assistance of large-scale equipment, and can easily achieve the doping ratio of the heavy metal complex unit in the phosphorescent polymer by controlling the ratio of the polymer and the heavy metal complex unit, thereby ensuring the product consistency of the phosphorescent polymer and facilitating the mass production of the phosphorescent polymer.

[0101] The third aspect of the present invention further provides an organic electroluminescent device, wherein the organic electroluminescent device comprises a light-emitting layer (EML), wherein the light-emitting layer comprises the phosphorescent polymer in the first aspect.

[0102] Based on the advantages of the phosphorescent polymer of the first aspect of the present invention, the organic electroluminescent device of the present invention not only has excellent luminescent properties and electrical properties, but also has excellent performance in terms of product consistency and product diversity.

[0103] The organic electroluminescent device may be a red organic electroluminescent device, a green organic electroluminescent device or a blue organic electroluminescent device. The organic electroluminescent device may further include at least one of a hole injection layer, a hole transport layer and an electron blocking layer located on a first side of the light-emitting layer, and an anode. The organic electroluminescent device may further include at least one of a hole blocking layer, an electron transport layer and an electron injection layer located on a second side of the light-emitting layer, and a cathode. The first side and the second side of the light-emitting layer may be opposite sides.

[0104] The phosphorescent polymer of the present invention is described in more detail below through specific examples.

[0105] Preparation of phosphorescent polymer Polymer-1

[0106] 1) Preparation of polymer units

[0107]

[0108] Synthesis of A2: Under nitrogen atmosphere, 20 mmol of A1 was dissolved in 500 ml of anhydrous DMF solution, 100 mmol of POCl3 was added dropwise at 0°C, and the reaction was allowed to proceed for 30 minutes. The ice bath was removed, the reaction was allowed to proceed for 2 hours at room temperature, and 300 mL of water was added to quench the reaction. The mixture was extracted with dichloromethane (3 x 30 mL), the organic phases were combined, washed three times with water, dried over anhydrous sodium sulfate, filtered, and concentrated. The crude product was recrystallized with dichloromethane: petroleum ether to obtain 16 mmol of the product. MS (atmospheric pressure solid analysis probe ion source, ASAP) = 436.2.

[0109] Synthesis of A3: Under nitrogen atmosphere, 10 mmol of compound A2 was dissolved in 300 mL of anhydrous THF, cooled to -78°C, 16 mmol of methylene triphenylphosphine (Wittig reagent) was added dropwise, and the mixture was returned to room temperature and reacted for 16 h. 100 mL of water was added to quench the reaction, and the mixture was extracted with dichloromethane (3 x 30 mL). The organic phases were combined, washed three times with water, dried with anhydrous sodium sulfate, filtered, and concentrated. Column chromatography was used for separation, and dichloromethane: n-hexane = 5:1. 9 mmol of the product was obtained. MS (ASAP) = 434.2.

[0110]

[0111] The synthesis method of B2 is the same as that of A2, except that reactant A1 is replaced by B1, MS (ASAP) = 516.1.

[0112] The synthesis method of B3 is the same as that of A3, except that reactant A2 is replaced by B2, MS (ASAP) = 512.1.

[0113] Synthesis of B4: B3 (6 mmol) was dissolved in anhydrous THF (20 mL), and an ethanol solution of trimethylamine (9 mmol, 30% ethanol solution) was added to produce a large amount of white precipitate.

[0114]

[0115] Wash with THF and n-hexane and dry. The product is 4.8 mmol of white solid. MS (ASAP) = 506.3

[0116] Synthesis of TP: Add A3 (3 mmol), B4 (3 mmol) and AIBN (30 mg) to a Schlenk reaction bottle, evacuate and fill with nitrogen for 3 times, add 6 mL of ultrapure NMP under N2 protection, and react at 75 ° C for 24 hours. Pour in 20 mL of methanol and collect the solid by filtration. The crude product was re-dissolved in dichloromethane (5 mL), filtered with a 0.45 μm PTFE syringe filter, and then added dropwise to anhydrous methanol (20 mL). The solid was collected by centrifugation and repeatedly washed with methanol to remove residual organic monomers. H NMR spectrum 1 HNMR (CDCl3, 400MHz, δ): 8.1-7.8 (br), 7.8-7.7 (br), 7.6 (br), 7.4-6.9 (br), 4.0 (br), 3.2 (br), 0.8-0.1 (m), 0.9 (br). The triplet energy level (T1) of TP is 2.70 eV, and x:y=47:53 (x, y are the mass percentages of the blocks represented). Wherein, br is a broad peak and m is a multiple peak.

[0117] 2) Preparation of heavy metal complex units

[0118]

[0119] Synthesis of C2: Under nitrogen atmosphere, C1 (1 mmol) and hydrated iridium trichloride (0.5 mmol, Ir: 55%) were added to a SCHLENK reaction bottle, and the mixture was pumped 3 times. A mixed solvent of ethylene glycol ether and water (20 mL, 3:1) was added, and the mixture was heated to 110°C for 16 hours. After cooling to room temperature, the reaction solution was poured into 100 mL of ice brine, and a large amount of precipitation was precipitated. The solid was collected by filtration, washed with water (3×20 mL), washed with n-hexane (3×20 mL), and dried to obtain the corresponding dichloro bridge complex precursor Ir-dFppy-dimer (0.178 g, 84%), which was directly used for the next step without separation and purification. Under nitrogen atmosphere, the synthesized Ir-dFppy-dimer (0.18 g) was added to the SCHLENK reaction bottle, evacuated 3 times, tetrabutylammonium cyanide (2 mmol) and dichloromethane (15 mL) were added, and heated to 40 ° C for 15 hours. After cooling to room temperature, it was concentrated, and the crude product was purified using a silica gel column, and the eluent was dichloromethane: methanol (10:1, v / v). The product was a yellow solid (0.3 mmol).

[0120] 3) Preparation of phosphorescent polymer Polymer-1

[0121]

[0122] Synthesis of Polymer-1: One equivalent of TP was dissolved in a THF-H2O mixed solution (5 mL, 1:1, v:v), and an aqueous solution of C2 (2 mL) was slowly added dropwise to control the mass doping concentration of the metal complex C2 to be 10% (m C2 / (m C2 +m TP )), stirred at room temperature in the dark for 1-4 h. Extracted with H2O+CH2Cl2 for 3 times, combined the organic layers, dried, concentrated, and washed with deionized water for 3 times to obtain Polymer-1.

[0123] 1 H NMR (CDCl3, 400MHz, δ): 8.0-7.9(m), 7.8-7.7(m), 7.5(br), 7.4-6.9(m), 4.0(br), 3.2(br), 0.8-0.1(m), 0.9(br);

[0124] GPC (gel permeation chromatography): Mw (weight average molecular weight) = 1.7 × 10 4 g mol –1, PDI (molecular weight distribution) = 1.5. x:y:z = 41.4:33.8:24.8 (x, y, z are the mass percentages of the blocks represented).

[0125] Example 1

[0126] The light-emitting device of this embodiment is prepared using the above-prepared Polymer-1 as a light-emitting layer material.

[0127] The light-emitting device structure includes an ITO anode, a hole injection layer PEDOT:PSS (40 nm), a light-emitting layer (25 nm), an electron transport layer TPBi (60 nm), an electron injection layer LiF (1 nm) and a cathode Al (100 nm) in sequence.

[0128] Example 2

[0129] The only difference between Example 2 and Example 1 is that the light-emitting layer material of the device in Example 2 is Polymer-2. The preparation method of Polymer-2 is basically the same as that of Polymer-1, except that in step 3), the mass doping concentration of the metal complex C2 is 0.2%.

[0130] Example 3

[0131] The only difference between Example 3 and Example 1 is that the light-emitting layer material of the device in Example 3 is Polymer-3. The preparation method of Polymer-3 is basically the same as that of Polymer-1, except that in step 3), the mass doping concentration of the metal complex C2 is 0.4%.

[0132] Example 4

[0133] The only difference between Example 4 and Example 1 is that the light-emitting layer material of the device in Example 4 is Polymer-4. The preparation method of Polymer-4 is basically the same as that of Polymer-1, except that in step 3), the mass doping concentration of the metal complex C2 is 0.6%.

[0134] Example 5

[0135] The only difference between Example 5 and Example 1 is that the light-emitting layer material of the device in Example 5 is Polymer-5. The preparation method of Polymer-5 is basically the same as that of Polymer-1, except that in step 3), the mass doping concentration of the metal complex C2 is 0.8%.

[0136] Example 6

[0137] The only difference between Example 6 and Example 1 is that the light-emitting layer material of the device in Example 6 is Polymer-6. The preparation method of Polymer-6 is basically the same as that of Polymer-1, except that in step 3), the mass doping concentration of the metal complex C2 is 1.0%.

[0138] Example 7

[0139] The only difference between Example 7 and Example 1 is that the light-emitting layer material of the device in Example 7 is Polymer-7. The preparation method of Polymer-7 is basically the same as that of Polymer-1, except that in step 3), the mass doping concentration of the metal complex C2 is 4.0%.

[0140] Example 8

[0141] The only difference between Example 8 and Example 1 is that the light-emitting layer material of the device in Example 8 is Polymer-8. The preparation method of Polymer-8 is basically the same as that of Polymer-1, except that in step 3), the mass doping concentration of the metal complex C2 is 5.0%.

[0142] Example 9

[0143] The only difference between Example 9 and Example 1 is that the light-emitting layer material of the device of Example 9 is Polymer-9. The preparation method of Polymer-9 is basically the same as that of Polymer-1, except that in step 3), the mass doping concentration of the metal complex C2 is 7.0%.

[0144] Example 10

[0145] The only difference between Example 10 and Example 1 is that the light-emitting layer material of the device of Example 10 is Polymer-10. The preparation method of Polymer-10 is basically the same as that of Polymer-1, except that in step 3), the mass doping concentration of the metal complex C2 is 13.0%.

[0146] Embodiment 11

[0147] The only difference between Example 11 and Example 1 is that the light-emitting layer material of the device of Example 11 is Polymer A1. The preparation method of Polymer A1 can be specifically carried out by using the corresponding raw material reference preparation method of Polymer-1. In Polymer A1, the mass doping concentration of the metal complex is 2%.

[0148]

[0149] Example 12

[0150] The only difference between Example 12 and Example 11 is that the light-emitting layer material of the device of Example 12 is Polymer A2. The preparation method of Polymer A2 is basically the same as that of Polymer A1, except that the mass doping concentration of the metal complex is 4.0%.

[0151] Example 13

[0152] The only difference between Example 13 and Example 11 is that the light-emitting layer material of the device of Example 13 is Polymer A3. The preparation method of Polymer A3 is basically the same as that of Polymer A1, except that the mass doping concentration of the metal complex is 6.0%.

[0153] Embodiment 14

[0154] The only difference between Example 14 and Example 11 is that the light-emitting layer material of the device of Example 14 is Polymer A4. The preparation method of Polymer A4 is basically the same as that of Polymer A1, except that the mass doping concentration of the metal complex is 8.0%.

[0155] Embodiment 15

[0156] The only difference between Example 15 and Example 1 is that the light-emitting layer material of the device in Example 15 is Polymer B1. The preparation method of Polymer B1 can be specifically carried out by using the corresponding raw materials in reference to the preparation method of Polymer-1. In Polymer B1, the mass doping concentration of the metal complex is 2%.

[0157]

[0158] Example 16

[0159] The only difference between Example 16 and Example 15 is that the light-emitting layer material of the device of Example 16 is Polymer B2. The preparation method of Polymer B2 is basically the same as that of Polymer B1, except that the mass doping concentration of the metal complex is 4.0%.

[0160] Embodiment 17

[0161] The only difference between Example 17 and Example 15 is that the light-emitting layer material of the device of Example 17 is Polymer B3. The preparation method of Polymer B3 is basically the same as that of Polymer B1, except that the mass doping concentration of the metal complex is 6.0%.

[0162] Embodiment 18

[0163] The only difference between Example 18 and Example 15 is that the light-emitting layer material of the device of Example 18 is Polymer B4. The preparation method of Polymer B4 is basically the same as that of Polymer B1, except that the mass doping concentration of the metal complex is 8.0%.

[0164] Comparative Example 1

[0165] The only difference between Comparative Example 1 and Example 1 is that the light-emitting layer material of the device in Comparative Example 1 is obtained by solid-state mixing and stirring of C2 and TP, wherein the mass doping concentration of C2 is 10%.

[0166] Comparative Examples 2-6

[0167] The only difference between the devices of Comparative Examples 2-6 and Example 1 is that the light-emitting layer materials of the devices of Comparative Examples 2-6 are obtained by solid-state mixing and stirring of C2 and TP, wherein the mass doping concentration of C2 is 0.2%, 0.4%, 0.6%, 0.8% and 1.0% respectively according to Comparative Examples 2-6.

[0168] Comparative Example 7

[0169] The only difference between the device of this comparative example and Example 1 is that the light-emitting layer material of the device of comparative example 7 is the following compound. In the process of using the heavy metal complex as a monomer to prepare the following compound, the materials are added according to the target mass percentage ratio of the blocks represented by x and y in the target product of 99.8:0.2 (wherein the molar ratio of the raw material for providing the block represented by x to the raw material for providing the block represented by y is 99.9:0.1). The structural formula of the prepared compound is shown below, GPC: Mw = 2.2×10 4 g mol -1 , PDI=1.6.

[0170]

[0171] Comparative Example 8

[0172] The only difference between the device of this comparative example and comparative example 7 is that the light-emitting layer material of the device of comparative example 8 is the following compound. In the process of preparing the following compound using the heavy metal complex as a monomer, the materials are added according to the target mass percentage ratio of the blocks represented by x and y in the target product of 99.6:0.4 respectively (wherein the molar ratio of the raw material for providing the block represented by x to the raw material for providing the block represented by y is 99.85:0.15). The prepared compound has GPC:Mw=2.2×10 4 g mol –1 ,PDI=1.6.

[0173]

[0174] Comparative Example 9

[0175] The only difference between the device of this comparative example and comparative example 7 is that the light-emitting layer material of the device of comparative example 9 is the following compound. In the process of using the heavy metal complex as a monomer to prepare the following compound, the materials are added according to the target mass percentage ratio of the blocks represented by x and y in the target product of 99.4:0.6 respectively (wherein the molar ratio of the raw material for providing the block represented by x to the raw material for providing the block represented by y is 99.8:0.2). The prepared compound has a GPC:Mw=2.2×10 4 g mol –1 ,PDI=1.6.

[0176]

[0177] Comparative Example 10

[0178] The only difference between the device of this comparative example and comparative example 7 is that the light-emitting layer material of the device of comparative example 10 is the following compound. In the process of using the heavy metal complex as a monomer to prepare the following compound, the materials are added according to the target mass percentage ratio of the blocks represented by x and y in the target product of 99.2:0.8 respectively (wherein the molar ratio of the raw material for providing the block represented by x to the raw material for providing the block represented by y is 99.75:0.25). The prepared compound has a GPC:Mw=2.2×10 4 g mol –1 ,PDI=1.6.

[0179]

[0180] Comparative Example 11

[0181] The only difference between the device of this comparative example and comparative example 7 is that the light-emitting layer material of the device of comparative example 11 is the following compound. In the process of preparing the following compound using the heavy metal complex as a monomer, the materials are added according to the target mass percentage ratio of the blocks represented by x and y in the target product of 99.0:1.0 respectively (wherein the molar ratio of the raw material for providing the block represented by x to the raw material for providing the block represented by y is 99.7:0.3). The prepared compound has a GPC:Mw=2.2×10 4 g mol –1 ,PDI=1.6.

[0182]

[0183] Test example

[0184] 1. Perform photoluminescence (PL) spectrum detection on the phosphorescent polymers of Examples 1-6 and the phosphorescent polymers of Comparative Examples 7-11.

[0185] Figure 1 PL spectrum diagram of the device of Example 1 of the present invention. Figure 1 It can be seen that the device of Example 1 has a light emission peak at around 465 nm.

[0186] Figure 2 PL spectra of the devices of Examples 2-6 of the present invention, Figure 3 PL spectra of devices of comparative examples 7-11 of the present invention.

[0187] like Figure 2 As shown, by Figure 2 It can be seen that as the doping amount of the metal complex C2 increases, the peak intensity of the phosphorescence spectrum increases in proportion. Therefore, it is proved that the phosphorescent polymer of the present invention can accurately control the spectrum even at extremely low doping concentrations.

[0188] and Figure 3 In the comparative example, although the amount of raw materials was adjusted in proportion according to the target doping concentration during the preparation process, the peak intensity of the phosphorescence spectrum finally obtained could not achieve a proportional increase. Therefore, when a polymerization reaction is carried out including a heavy metal complex unit as a monomer to introduce the heavy metal complex unit into the main chain or side chain of the polymer, the reaction process is difficult to control, and it is difficult to obtain a target phosphorescent polymer that meets the expected doping. That is, in the preparation process of the comparative example, as the doping concentration of the raw materials changes, the peak intensity of the phosphorescence spectrum cannot achieve a proportional increase.

[0189] Therefore, through Figure 2 and Figure 3 It can be seen from the comparison that the phosphorescent polymer of the present invention can accurately control the doping of the light-emitting unit and the main body to achieve production consistency of the product.

[0190] 2. The current efficiency of Examples 1, 13, 16 and Comparative Example 1 at different brightnesses was tested.

[0191] Figure 4 It is a comparison chart of the brightness-current efficiency curves of the device of Example 1 of the present invention and the device of Comparative Example 1. Figure 5 It is a comparison chart of the brightness-current efficiency curves of the device of Example 1, the device of Example 13 and the device of Example 16 of the present invention.

[0192] from Figure 4 It can be seen that the current efficiency of the device in Example 1 is significantly better than that of the device in Comparative Example 1;

[0193] from Figure 5 It can be seen that with the increase of brightness, the attenuation amplitude of the current efficiency of Examples 13 and 16 is significantly lower than that of Example 1. Therefore, in the phosphorescent polymer, a more suitable branching unit helps to prevent quenching and plays a role in reducing the efficiency roll-off.

[0194] 3. The parameters of Eff., Von, FHWM, LT90 and Main Peak of the devices in the embodiments and comparative examples were tested, and the results are shown in Table 1. Eff. is the current efficiency at 740 nit, in cd / A; Von is the voltage at 1 nit, in V; LT90 is the time required for the lifetime to decay to 90% of the initial brightness at a current of 30 J, in h; FHWM is the half-peak width of the spectrum at 740 nits, in nm; Main Peak is the maximum emission wavelength of the spectrum at 740 nits, in nm.

[0195] Eff., Von, FHWM, and Main Peak are tested using Foster IVL testing equipment; LT90 is tested using an OLED aging life tester.

[0196] Table 1

[0197]

[0198]

[0199] From Table 1, we can see that:

[0200] 1. The luminous efficiency, driving voltage and luminous life of the device in Example 1 are significantly better than those of the device in Comparative Example 1. The reason is that the luminescent material in the device in Comparative Example 1 is only physically mixed in the solid phase through the luminescent unit C2 and the main body TP, and no electrostatic adsorption occurs between the luminescent unit and the main body. Therefore, there is a phase separation problem, which ultimately leads to poor performance of the device; Figure 4 This is consistent with the conclusions obtained in;

[0201] Similarly, the comparison between Examples 2-6 and Comparative Examples 2-6 also shows that when the ratio of the light-emitting unit to the main body is the same, the light-emitting layer material of the present invention using the light-emitting unit and the main body for electrostatic adsorption helps to significantly improve the luminous efficiency, driving voltage and luminous life of the light-emitting device;

[0202] 2. According to the comparison between Examples 2-6 and Comparative Examples 7-11, the luminous efficiency, driving voltage and luminous life of the light-emitting devices of the Examples are significantly better than those of the Comparative Examples. Therefore, compared with the phosphorescent polymer of the present invention, the phosphorescent polymer obtained by polymerization reaction with heavy metal complex units as monomers is not only difficult to achieve precise control of the doping ratio, but also difficult to have satisfactory performance in terms of electrical properties;

[0203] 3. According to the comparison of Examples 1-18, it can be seen that by controlling the doping ratio of the heavy metal light-emitting unit to the main body, the relevant electrical properties of the light-emitting device can be significantly adjusted;

[0204] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A phosphorescent polymer, characterized in that: The phosphorescent polymer comprises a polymer unit and a heavy metal complex unit, wherein the polymer unit comprises a polymer main chain unit and a first branch chain unit; The first branching unit includes a quaternary amine cation; The phosphorescent polymer comprises N first blocks as shown in Formula 1, N≥1, Wherein, A is a repeating unit of the polymer main chain unit, R a + is the first branching unit including the quaternary ammonium cation, M - A heavy metal complex unit comprising the heavy metal complex anion, the heavy metal complex unit is capable of emitting phosphorescence, a1≥1; The phosphorescent polymer further includes M second blocks as shown in Formula 2, M≥1, Among them, a2≥1; The phosphorescent polymer comprises a third block of T species as shown in Formula 3 and / or a fourth block of Q species as shown in Formula 4, wherein T≥1, Q≥1, Wherein, B and C are repeating units of the polymer main chain unit, R b is the second branch unit, b≥1, c≥1; The quaternary ammonium cation has a structure shown in Formula 5, Wherein, R1 to R3 are independently selected from C1 to C30 alkyl groups; The first branching unit and / or the second branching unit includes at least one group represented by Z-1, Z-2, Z-3, Z-4, Z-5, Z-6, Z-7 and Z-8:

2. The phosphorescent polymer according to claim 1, characterized in that The total mass proportion of the third block and the fourth block in the phosphorescent polymer is greater than or equal to 50% and less than or equal to 80%.

3. The phosphorescent polymer according to claim 1, characterized in that The mass proportion of the second block in the phosphorescent polymer is greater than or equal to 10% and less than or equal to 45%.

4. The phosphorescent polymer according to claim 1, characterized in that The mass proportion of the first block in the phosphorescent polymer is greater than or equal to 5% and less than or equal to 10%.

5. The phosphorescent polymer according to claim 1, characterized in that The molar percentage of the heavy metal complex unit in the phosphorescent polymer is less than or equal to 10%.

6. The phosphorescent polymer according to claim 1, characterized in that The total mass proportion of the third block and the fourth block in the phosphorescent polymer is greater than or equal to 50% and less than or equal to 80%; The mass proportion of the second block in the phosphorescent polymer is greater than or equal to 10% and less than or equal to 45%; The mass proportion of the first block in the phosphorescent polymer is greater than or equal to 5% and less than or equal to 10%; The molar percentage of the heavy metal complex unit in the phosphorescent polymer is less than or equal to 10%.

7. The phosphorescent polymer according to claim 6, characterized in that The first excited triplet energy level of the polymer unit is greater than or equal to 2.62 eV.

8. The phosphorescent polymer according to claim 7, characterized in that The polymer main chain unit is a non-conjugated structure.

9. The phosphorescent polymer according to claim 8, characterized in that The polymer main chain unit is formed by polymerizing at least one of an aryl phosphine oxide derivative monomer and an aryl ether derivative monomer.

10. The phosphorescent polymer according to claim 9, characterized in that The phosphorescent polymer has a structure shown in Formula 6 or Formula 7: Among them, a>1, b>1, c>1, d>1, n>1.

11. The phosphorescent polymer according to claim 9, characterized in that The phosphorescent polymer has a structure shown in Formula 8: Among them, x>1, y>1, z>1.

12. The phosphorescent polymer according to claim 11, characterized in that The heavy metal complex unit includes an iridium cyanide complex.

13. A method for preparing the phosphorescent polymer according to any one of claims 1 to 12, characterized in that: include: A solution including a polymer and a heavy metal complex is stirred to obtain the phosphorescent polymer, wherein the polymer is used to provide the polymer unit, and the heavy metal complex is used to provide the heavy metal complex unit.

14. An organic electroluminescent device, characterized in that: The invention comprises a light-emitting layer, wherein the light-emitting layer comprises the phosphorescent polymer according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Organic electroluminescent element, organic electroluminescent element material, display device, and lighting device

    JP2010141008A

  • Polymeric anions / cations

    US20100059740A1